The Exegesis of the «Cornerstone» in the Context of the Parable of the Wicked Tenants (Mt 21,33-44) in the Works of Hilary of Poitiers: Reflections on the Temple of the New Creation - Alba López, Almudena (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2023)
Hilary of Poitiers carries out a superficial analysis of the parable of the wicked tenants (Mt 21,33-44) in his Commentarium in Matthaeum. Nevertheless, the main motifs and elements that make up this parable are repeatedly used throughout the entirety of his works in the manner of a mise en abyme structured based on Pauline theology. In particular, we will analyse how Hilary uses the motif of the «cornerstone» with regards to Christ as the basis for a new Temple in the context of the new creation he inaugurates as the last Adam, and which is an image of his Church.